Characteristics of hepatocellular carcinoma arising from Fontan‐associated liver disease. Issue 7 (30th April 2020) - Sagawa, Takaomi; Kogiso, Tomomi; Sugiyama, Hisashi; Hashimoto, Etsuko; Yamamoto, Masakazu; Tokushige, Katsutoshi
Abstract : Aim: Hepatocellular carcinoma (HCC) can arise from Fontan‐associated liver disease (FALD); this is known as FALD‐HCC. The clinical features of FALD‐HCC are unclear. Thus, we examined the incidence and clinical characteristics of FALD‐HCC. Methods: From 1972 to 2019, 122 patients developed liver disease after undergoing Fontan procedures. HCC was diagnosed in 12 (9.8%) FALD patients. We compared FALD‐HCC and non‐HCC patients. Results: The incidence of HCC was 0.8% and 2.9% in FALD 10 and 20 years after the Fontan procedure, respectively. The median age of patients at diagnosis of HCC was 32.5 years (range 20.6–46.1 years), and seven of the 12 patients were men. Patients with FALD‐HCC had a higher incidence of liver cirrhosis and polysplenia than non‐HCC patients. Liver tumors were detected as single nodules in eight patients, and the median diameter was 47 mm (range 11–105 mm). HCC was treated by surgical resection in two patients, transcatheter arterial chemoembolization or chemotherapy in three patients, and proton beam therapy in four patients. Three patients could not be treated because of their poor condition. Four patients died of liver/cardiac failure and HCC, and HCC was controlled in three patients. The survival rate after 25 years was significantly lower in patients with FALD‐HCC than non‐HCC patients (68.6% vs. 97.9%, respectively; P  < 0.01). Conclusions: Of the 122 patients with FALD, 12 developed HCC 20 years after surgery. Because complications of HCC are associated with poor prognosis, constant surveillance for HCC should begin 10 years after surgery.